How do schools in Indonesia fight against cyberbullying? - Wulandari, Aprilianti; AW, Suranto (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
The development of highly advanced technology has changed the pattern of people's lives in fulfilling information needs. All forms of information obtained will spread very quickly and even difficult to control. We cannot avoid that currently people from all walks of life are increasingly "lulled" by the sophistication of technology such as cellphones to smartphones which are of course equipped with various applications that make it easier for users. However, this convenience is not accompanied by control from various parties, causing a negative impact commonly called Cyberbullying. This paper describes how cyberbullying cases affect school-age children so that the participation of related parties such as schools is needed. In addition, this paper also describes the policies implemented in schools to deal with cyberbullying cases sourced from several writings or articles. The research method used is library research where researchers collect various sources from several research results and libraries. For this research, researchers took various sources from Google Scholar. From the articles, it is recommended that some policies can be offered to schools to anticipate and prevent Cyberbulling behavior.